Synthesis of disulfides and 3-sulfenylchromones from sodium sulfinates catalyzed by TBAI - Zhang, Zhenlei; Wang, Ying; Pan, Xingxing; Zhang, Manqi; Zhao, Wei; Li, Meng; Zhang, Hao (Beilstein Journal of Organic Chemistry, 2025)
A new synthetic method for disulfides and 3-sulfenylchromones is reported. This innovative approach is based on the tetrabutylammonium iodide (TBAI)/H2SO4 reduction system using sodium sulfinate as key component, thus eliminating the need for thiols and redox reagents commonly used in traditional methods. Various disulfides and 3-sulfenylchromones were obtained in moderate to excellent yields through this methodology. Mechanistic studies indicate that thiosulfonates play an important role in the reaction process.
Keywords: disulfides; sodium sulfinates; 3-sulfenylchromones; TBAI; thiosulfonates